Bundling as strategy of tourist attraction based on natural and cultural tourism in the ex-Surakarta residency - Yuliari, Giyah; Riyadi, Bambang (Journal of Sustainable Tourism and Entrepreneurship, 2019)
Purpose: Indonesia has many tourist attractions, but not all places are well known, which makes them have no visitors. The objectives of this study are to find out how the condition of attractions in each district/city in the Surakarta Residency and how to increase tourist visits to tourist attractions. Research methodology: The research design is qualitative research. Data are presented in descriptive form, with in-depth and flexible analysis. Sampling by purposeful sampling, the sample chosen depends on the research objectives without regard to the ability of the generalist. The method used is implementing a bundling marketing strategy, which issues product bundling and price bundling in the form of several travel packages. Results: There are two tourist attractions that are already developing and which are still in the form of potential. Travel agents can offer tourist attractions that have developed to tourists by bundling through tour packages. Tourist attractions that are still potential but attractive can be offered as well. So that all tourist attractions will get tourist visits. Limitation: This research was conducted at the Ex-Residency of Surakarta, in Central Java, Indonesia. There are many types of tourist destinations, such as cultural, natural, educational, religious, sport, museum, shopping and culinary heritage tours. So that the bundling is only valid for the area. Contribution: Application of bundling is one way to determine the selling price of a product in this case a tourism product, so that tourism products in the form of tour packages can be sold at attractive prices, which are expected to increase tourist visits. Keywords: Bundling strategy, Tourist attraction, Tourist collaboration, Spirit of gotong royong, Developing tourism